The PNPLA3 variant associated with fatty liver disease (I148M) accumulates on lipid droplets by evading ubiquitylation. Issue 4 (26th August 2017) - BasuRay, Soumik; Smagris, Eriks; Cohen, Jonathan C.; Hobbs, Helen H.
Abstract : A sequence variation (I148M) in patatin‐like phospholipase domain‐containing protein 3 (PNPLA3) is strongly associated with fatty liver disease, but the underlying mechanism remains obscure. In this study, we used knock‐in (KI) mice ( Pnpla3 148M/M ) to examine the mechanism responsible for accumulation of triglyceride (TG) and PNPLA3 in hepatic lipid droplets (LDs). No differences were found between Pnpla3 148M/M and Pnpla3 +/+ mice in hepatic TG synthesis, utilization, or secretion. These results are consistent with TG accumulation in the Pnpla3 148M/M mice being caused by impaired TG mobilization from LDs. Sucrose feeding, which is required to elicit fatty liver in KI mice, led to a much larger and more persistent increase in PNPLA3 protein in the KI mice than in wild‐type (WT) mice. Inhibition of the proteasome (bortezomib), but not macroautophagy (3‐methyladenine), markedly increased PNPLA3 levels in WT mice, coincident with the appearance of ubiquitylated forms of the protein. Bortezomib did not increase PNPLA3 levels in Pnpla3 148M/M mice, and only trace amounts of ubiquitylated PNPLA3 were seen in these animals. Conclusion: These results are consistent with the notion that the 148M variant disrupts ubiquitylation and proteasomal degradation of PNPLA3, resulting in accumulation of PNPLA3‐148M and impaired mobilization of TG from LDs. (Hepatology 2017;66:1111‐1124).